Response of pullets to digestible lysine intake - De Araujo, J. A. [UNESP]; Sakomura, N. K. [UNESP]; Da Silva, E. P. [UNESP]; De Paula Dorigam, J. C. [UNESP]; Zanardo Donato, D. C. [UNESP]; Da Silva, J. H V; Fernandes, J. B K [UNESP] (My University, 2014)
The objective was to determine the efficiency of utilization of lysine and to describe the responses of pullets to different digestible lysine intakes using three mathematical functions to estimate an optimal intake maximizing body weight gain and feed conversion ratio. The trials were conducted using 2-6-, 8-12-, and 14-18-weekold birds and a completely randomized experimental design with eight treatments and six replicates. The digestible lysine levels ranged 3.20-10.67 g/kg (in 2-6-week-old animals), 2.24-7.48 g/kg (in 8-12-week-old animals), and 1.73-5.78 g/kg (in 14-18-week-old animals) and were obtained using a dilution technique. The efficiency of utilization was determined by a linear regression between lysine deposition and intake for pullets aged 2-4, 8-10, and 14-16 weeks. Three mathematical functions (quadratic polynomial, broken-line, and broken-line with quadratic ascending function) were used to fit the body weight gain and feed conversion responses. The optimal digestible lysine intake was obtained from the first intercept of the quadratic curve with the broken-line plateau. Based on the body weight gain, the responses obtained from the broken-line function and the broken-line with quadratic ascending were similar to those from the quadratic polynomial function. The feed conversion ratio from the first intercept of the quadratic curve with the broken-line plateau was similar to the value obtained from the broken-line with quadratic ascending function only in 2-6-week-old animals. The digestible lysine intakes required to optimize the body weight gain and feed conversion ratio responses were 202, 338, and 300 and 146, 312, and 259 mg/day and the efficiencies were 80, 76, and 80% for 2-6-, 8-12-, and 14-18-week-old animals, respectively.
Keywords: Age; Amino acid; Feed conversion ratio; Growth; Mathematical functions